Cuclí Cuclí: Science With No Hiding Places (2019)
Cuclí was born as a strategy to communicate science throughout Colombia, it is thought as a method so that the children of the country do not continue to think that science is only for a few, leads to low-income regions and is implemented in schools, has been transformed over time, more visual, less text, to capture the attention of children. It was possible to obtain a more independent learning on the part of the children, without having an adult watching, because it comes out from the curiosity of the little ones.